A study on the adequacy of the Sale of Drugs Act 1952 in governing the retail sale of pharmaceutical products by foreigners in Kuala Lumpur / Rohaida Zakaria - Zakaria, Rohaida (2017)
The retail sales of pharmaceutical products by foreigners are one of the problems faced by the Pharmacy Enforcement Branch. Unregistered products such as over the counter products, traditional products and health supplements are products that were commonly seized during inspections and raids. Currently, there are problems that arise from the state of existing laws and regulations pertaining to the sale of pharmaceutical products by foreigners. The control of the retail sale of pharmaceutical products except for the scheduled poisons is silent in the existing laws. For the issue that exists to be resolved, a more stringent rule needs to be regulated and a clear procedure should be established. This study aims to examine the adequacy of the provision in the Sale of Drugs Act 1952, to identify and analyse the problems encountered relating to the retail sales of pharmaceutical products by foreigners, particularly in Kuala Lumpur. The aims are to propose recommendation on the existing regulatory measures to minimise the problems concerning the retail sale of pharmaceutical products. The methodology used is looking into relevant kinds of literature, articles, reports, laws and regulations as well as semi-structured interviews with selected individuals having the necessary experience and competent authority. The result of the research corresponds to the objectives and answered most of the queries and offered a proposal for rectifications.